2016
DOI: 10.3390/diagnostics6030031
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Diagnostics for Improving Maternal Health in South Africa

Abstract: Improving maternal health is a global priority, particularly in high HIV-endemic, resource-limited settings. Failure to use health care facilities due to poor access is one of the main causes of maternal deaths in South Africa. “Point-of-care” (POC) diagnostics are an innovative healthcare approach to improve healthcare access and health outcomes in remote and resource-limited settings. In this review, POC testing is defined as a diagnostic test that is carried out near patients and leads to rapid clinical dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Despite this high communicable disease burden in South Africa, our review revealed that South Africa offers fewer POC tests for communicable diseases than the USA, which has a low disease burn [12]. Prompt access to these new POC tests is encouraged in high disease-burdened and resource-limited settings [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this high communicable disease burden in South Africa, our review revealed that South Africa offers fewer POC tests for communicable diseases than the USA, which has a low disease burn [12]. Prompt access to these new POC tests is encouraged in high disease-burdened and resource-limited settings [13].…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation of POC diagnostics in resource-limited settings is based on its compliance with the WHO quality-ASSURED (Affordable, Sensitive, Specific, User friendly, Rapid and to enable treatment at first visit and Robust, Equipment free and Delivered to those who need it) criteria [12,13,18,19]. The entire process of POC diagnostics, from the pre-analytic through the analytic and post-analytic phases, has hidden reliability risks, which include false-positive and false-negative test results, which can lead to gross medical errors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although current programmes could be enhanced by the introduction of POC testing [41,42] to address some existing challenges [43], it has been suggested [44,45] that certain factors need to be considered before POC implementation: Clinic flows, diagnostic accuracy, staff training, quality control, and turnaround times. In South Africa, multiple strategies [46] have previously been used to overcome high patient burden and staff shortages [7] with respect to rapid HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of improved accessibility to POC diagnostics services are significant. This review demonstrates the impacts of POC testing services such as enabling rapid diagnosis and informing prompt clinical decisions [ 4 , 6 , 11 , 12 , 14 , 16 , 17 , 20 , 21 , 25 , 26 , 27 , 77 , 78 , 79 ]. It also reveals that successful implementation of POC diagnostics services requires appropriate healthcare infrastructure, efficient supply chain management, quality systems management, enabling a policy framework and as well as geographical consideration during implementation [ 38 , 40 , 56 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…POC testing can shorten the time of clinical decision-making about additional testing or therapy, as delays are no longer caused by transport and preparation of clinical samples, and biochemical test results are rapidly available at the point of care [ 8 ]. Studies have shown that POC testing improves medical outcome and lowers the costs of seeking healthcare services in resource-limited settings [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%